L’expérience de l’espace dans les jeux vidéo et les récits numériques - Marie-Laure Ryan (Cahiers de Narratologie)
This article studies two conceptions of space in digital media: the first based on an emotional relation to space, and the second on a strategic relation. While the emotional conception constructs subjects on the basis of their affective relation to his environment, the strategic relation constructs them as possibility of action. The two conceptions are illustrated through the study of a variety of documents: autobiographical annotations of Google Earth photos, online worlds, video game maps, and Alternate Reality Games.